Diversity of the KIR gene cluster in an urban Brazilian population - Augusto, D. G. (2011)
The activity of natural killer cells depends on the balance between activating and inhibitory signals coming from their receptors. Among these are the killer cell immunoglobulin-like receptors (KIR) that recognize specific HLA class I allotypes. Here we characterized KIR genetic diversity and their HLA ligands in the population of Curitiba, Paraná State (n=164), and compared it with other worldwide populations. The distribution of 2DL4 alleles was also analyzed. The Curitiba population did not differ significantly from European and Euro-descendant populations, but as an admixed population showed higher genetic diversity. We found 27 KIR profiles, many of them uncommon in European populations, in agreement with the elevated historically recent gene flow in the study population. The frequencies of KIR genes and their respective HLA ligands were distributed independently and none of the analyzed individuals lacked functional KIR–HLA ligand combinations. KIR gene frequencies of 33 worldwide populations were consistent with geographic and ethnic distribution, in agreement with demography being the major factor shaping the observed gene content diversity of the KIR locus.